THE EFFECT OF CREDIT AND SAVINGS ON POVERTY REDUCTION, ECONOMIC GROWTH AS A MODERATING VARIABLE : EVIDENCE IN INDONESIA - Rofiqotul Khoiriyah, Ikhda; Dwi Riyanto, Feri; Karim, M Radinal; Munir, Misbahul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the role of economic growth as a moderating variable in the influence of credit and savings on poverty reduction in Indonesia. Using panel data from 34 provinces over the period 2015–2024 and employing the Moderated Regression Analysis (MRA) method, the findings indicate that credit has a significant negative effect on poverty, both directly and through interaction with economic growth. In contrast, savings alone do not significantly affect poverty, suggesting that savings behavior among the poor may function more as precautionary saving rather than productive investment. However, when interacting with economic growth, savings become significant in reducing poverty. Economic growth itself does not directly reduce poverty, reflecting a weak trickle-down effect and uneven distribution of benefits. Nevertheless, it strengthens the impact of both credit and savings on poverty alleviation. The study concludes that integrated policies promoting financial inclusion and equitable economic growth are essential for sustainable poverty reduction.